Modeling the spread risk of dengue vector Aedes albopictus caused by environmental factors in Shanghai China - Jiamin Wang; Yanfeng Gong; Junhui Huang; Ning Xu; Yu Zhou; Liyun Zhu; Liang Shi; Yue Chen; Qingwu Jiang; Yibiao Zhou (Asian Pacific Journal of Tropical Medicine, 2025)
Objective: To predict the distribution of dengue vector Aedes (Ae.) albopictus and identify high-risk areas for dengue fever transmission. Methods: Data on Ae. albopictus occurrences were collected from electronic databases. Ensemble models were developed to assess the impacts of climate, vegetation, and human activity on Ae. albopictus. The optimal ensemble model was then used to identify the distribution of suitable areas for Ae. albopictus. Results: After removing duplicate sites and retaining only one location per 100 m × 100 m grid, 189 Ae. albopictus breeding sites were identified. The optimal ensemble model revealed that Ae. albopictus exhibited higher breeding suitability in Shanghai under specific conditions: a normalized difference vegetation index of 0.1 to 0.6, maximum precipitation in the warmest month ranging from 400 mm to 470 mm, maximum temperature in the warmest month between 30.0 °C and 31.0 °C, and proximity to waterways within 0.5 km. The most suitable habitats for Ae. albopictus were primarily concentrated in Shanghai’s central urban areas and scattered across the inner suburban districts. Conclusions: The high-risk areas of Ae. albopictus are widely distributed throughout the central urban area and scattered across the inner suburban district of Shanghai, creating conditions conducive to the outbreak of dengue fever. It is essential to enhance targeted control measures for Ae. albopictus in the identified risk areas.